Wild Panax vietnamensis and Panax stipuleanatus markedly increase the genetic diversity of Panax notoginseng (Araliaceae) revealed by start codon targeted (SCoT) markers and ITS DNA barcode. (June 2016) - Xia, Pengguo; Guo, Hongbo; Zhang, Yu; Deyholos, Michael K.; Peng, Liang; Jia, Yanyan; Yan, Xijun; Liu, Yan; Liang, Zongsuo
Abstract: In order to evaluate whether the two wild species, Panax vietnamensis (from Vietnam) and Panax stipuleanatus (from primeval forest, Yunan Province) could markedly increase the genetic diversity of cultivated Panax notoginseng (Wenshan, Yunnan Province), both start codon targeted (SCoT) markers and internal transcribed spacer (ITS) DNA barcode were firstly employed in this genus. A total of 173 amplification bands were generated by 16 selected SCoT primers, in which 153 (89.5%) were polymorphic. Nei's gene-diversity indicated that the genetic diversity of three species ( h = 0.16 and I = 0.27) was obviously higher than that of P. notoginseng ( h = 0.09). Similarly, 38 different ITS sites out of 639 (5.9%) were detected among three species, but only one was different within 22 samples of P. notoginseng . Analysis of molecular variance (AMOVA) showed a greater proportion of genetic diversity existed within (61.3%) rather than among (38.7%) groups at genus level. In addition, P. vietnamensis had a closer relationship with P. notoginseng than P. stipuleanatus . These results would be significant for increasing the genetic diversity of P. notoginseng population by hybridization with P . vietnamensis and P . stipuleanatus, thus obtaining more varieties for future cultivar breeding and germplasm resources management. Highlights: Two wild Panax species markedly increased genetic diversity of Panax notoginseng. Variable ITS sites (5.9%) among 3 species were more than 0.05% in P. notoginseng. Panax vietnamensis had a closer relationship with P. notoginseng than Panax stipuleanatus.